Synthesis of fluorinated acyclic nucleoside phosphonates with 5-azacytosine base moiety - Pomeisl, Karel; Krečmerová, Marcela; Pohl, Radek; Snoeck, Robert; Andrei, Graciela (Tetrahedron, 2019)
With respect to the strong antiviral activity of (S)-1-[3-hydroxy-2-(phosphonomethoxy)propyl]-5-azacytosine various types of its side chain fluorinated analogues were prepared. The title compound, (S)-1-[3-fluoro-2-(phosphonomethoxy)propyl]-5-azacytosine (FPMP-5-azaC) was synthesised by the condensation reaction of (S)-2-[(diisopropoxyphosphoryl)methoxy)-3-fluoropropyl p-toluenesulfonate with a sodium salt of 5-azacytosine followed by separation of appropriate N 1 and O 2 regioisomers and ester hydrolysis. Transformations of FPMP-5-azaC to its 5,6-dihydro-5-azacytosine counterpart, amino acid phosphoramidate prodrugs and systems with an annelated five-membered imidazole ring, i.e. imidazo [1,2-a][1,3,5]triazine derivatives were also carried out. 1-(2-Phosphonomethoxy-3,3,3-trifluoropropyl)-5-azacytosine was prepared from 5-azacytosine and trifluoromethyloxirane to form 1-(3,3,3-trifluoro-2-hydroxypropyl)-5-azacytosine which was treated with diisopropyl bromomethanephosphonate followed by deprotection of esters. Antiviral activity of all newly prepared compounds was studied. FPMP-5-azaC diisopropyl ester inhibited the replication of herpes viruses with EC50 values that were about three times higher than that of the reference anti-HCMV drug ganciclovir without displaying cytotoxicity.
Keywords: Fluorinated nucleotides; Acyclic nucleoside phosphonates; Prodrugs; 5-Azacytosine; Phosphonates